Implementasi Metode Resitasi Melalui Pembuatan Video Presentasi Terhadap Aktivitas Belajar Siswa - IFA HIDAYAH (Madaris: Jurnal Guru Inovatif, 2022)
Student activities in learning greatly affect the process and learning outcomes. Based on the preliminary study, it is known that student activity in the learning process has not been maximized. It can be seen from the lack of student response during learning and the number of students who do not collect assignments. Factors causing this problem include students' difficulties in understanding the material, so they are unable to complete the tasks given by the teacher. The problem also comes from the teacher which is the limited time in face-to-face learning (PTMT). Hence, the learning material cannot be delivered completely. The purpose of applying the recitation method to make this video presentation is to increase student activity in learning, and the results of each student's video presentation can be used as a learning medium for other students. The research method used is descriptive quantitative. Based on the assessment results, it was found that there was an increase in student activity in learning. It could be seen from the increase in the percentage of students who collected assignments after the recitation method was applied to make video presentations. From the results of the previous assignment, there were only 18 students who worked out of 34 students. After applying this method, all students were active and collected the assignments. Therefore, there is an increase in the percentage of students working on assignments, from 52.9% to 100%.